FoMO dan Strategi Digital Marketing dalam Mendorong Minat Beli Skincare Impor - Siti Asriah Immawati; Humairoh Humairoh; Dadang Dadang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study is motivated by the rapid advancement of digital marketing and the increasing influence of psychological factors in shaping consumer behaviour, particularly among Generation Z, who are highly exposed to social media and global trends in imported skincare products. This phenomenon suggests that purchase decisions are not solely driven by digital marketing strategies but are also significantly influenced by emotional drivers such as Fear of Missing Out (FoMO). Accordingly, this study aims to analyse the effects of affiliate marketing, WhatsApp status, celebrity advertising, and FoMO on the purchase intention of Generation Z consumers in Tangerang City. Specifically, the study pursues five objectives: (1) to examine the effect of affiliate marketing on purchase intention; (2) to analyse the influence of WhatsApp status on purchase intention; (3) to investigate the impact of celebrity advertising on purchase intention; (4) to evaluate the effect of FoMO on purchase intention; and (5) to assess the simultaneous effects of all independent variables on purchase intention. This study adopts a quantitative approach using a survey method, with data collected through structured questionnaires administered to 250 respondents selected via accidental sampling. Data were analysed using multiple linear regression with the aid of SPSS software to examine the relationships among variables. The findings reveal that all independent variables exert a positive and statistically significant influence on purchase intention, with FoMO emerging as the most dominant predictor. These results underscore the greater role of psychological factors relative to digital marketing strategies in driving purchase intention among Generation Z consumers.The contribution of this study lies in integrating digital marketing strategies and psychological factors into a single empirical model, while also highlighting the growing importance of interpersonal digital communication, such as WhatsApp, in contemporary marketing contexts. From a practical perspective, the findings provide managerial implications for businesses to design marketing strategies that are not only informative but also capable of creating urgency and fostering emotional engagement among consumers.